Multimodality imaging predictors of appropriate ICD shock and mortality in adults with cardiac sarcoidosis. (3rd October 2022) - Hutt, E; Vega Brizneda, M; Aguilera, J; Wang, T K M; Taimeh, Z; Culver, D; Callahan, T; Tang, W; Jaber, W A; Cremer, P; Ribeiro, M; Jellis, C
Abstract: Background: Identifying patients with cardiac sarcoidosis (CS) who are at increased risk of sudden cardiac death (SCD) is imperative. Current guideline recommendations for implantable cardioverter-defibrillator (ICD) implantation in patients with CS are based on small observational studies and have not been validated in contemporary cohorts using multimodality cardiac imaging. Purpose: The aim of this study was to characterize a cohort of patients with tissue-proven cardiac sarcoidosis who underwent multimodality cardiac imaging and identify predictors of appropriate ICD shock and mortality. Methods: We retrospectively identified subjects with a diagnosis of CS established by clinical/imaging criteria, and tissue biopsy (N=273) seen at our tertiary care center between 2001 and 2021. Clinical characteristics and outcomes were collected from electronic medical records. The primary endpoint of interest was a composite of appropriate ICD shock and all-cause mortality. Secondary endpoints were individual rates of appropriate ICD shock and all-cause mortality. Cox proportional hazard regression analysis was used to identify independent predictors of the outcomes. Results: Mean age was 59±11 years and 40% were female. Isolated CS was found in 49 subjects (17.9%). The prevalence of traditional cardiovascular risk factors was low. Atrial fibrillation prevalence was high (41%). After a median follow-up of 7.9 years, the rate of appropriate ICD shock and all-cause mortality was 29% (N=79). The 5-year overall survival rate of 97.5%. Age, left ventricular ejection fraction (LVEF), and delayed gadolinium enhancement (DGE) in cardiac magnetic resonance (CMR) were independent predictors of the primary composite endpoint; LVEF and DGE in CMR were independent predictors of appropriate ICD-shock; and LVEF and baseline serum NT proBNP were independent predictors of overall mortality. An LVEF of 47% was identified as the optimal cutoff in predicting the primary composite endpoint. Presence of scar, inflammation or mismatch pattern in positron emission tomography were not significant predictors of the outcomes. Conclusion: In this large cohort of subjects with CS, we found that the presence of DGE in CMR was the strongest independent predictor of the composite endpoint of appropriate ICD-shock and mortality and of appropriate ICD-shock individually; LVEF by echocardiogram was an independent predictor of the primary and secondary endpoints with an optimal LVEF cutoff for predicting the composite endpoint of 47%. Funding Acknowledgement: Type of funding sources: None.